Anti-tumor effect of PTEN and its effect on inhibition of the bone tumor through the CD47-SIRPα signaling pathway: PTEN inhibits the bone tumor genesis - Zhang, Yi; Hao, Ji (Cellular and Molecular Biology, 2023)
This study aimed to explore the correlation between the expression of phosphatase and tensin homolog (PTEN), a tumor suppressor gene, and CD47-SIRPα signaling pathway, and clarify the underlying mechanisms of the bone tumor inhibition effect of PTEN. In this study, August x Copenhagen Irish (ACI) male rats were used, and 100μl of UMR-106 cell suspension (1´106 cells) was injected subcutaneously to induce the bone tumor model. The gene expression of PTEN, CD47 and SIRPα of both groups (control and bone tumor model) were analyzed by RT-PCR. For in vitro experiments, pEGFP-N1-PTEN plasmid was used to transfect the murine bone tumor UMR-106 and the human bone tumor KRIB cells. Also, we detected the invasiveness of the UMR-106 cells and KRIB cells after transfection. In this study, we observed that the gene expression of PTEN and SIRPα were significantly decreased in the ACI rats with bone tumors in comparison to the control group, however, the expression level of CD47 has been significantly increased. The tumor cells transfected with the pEGFP-N1-PTEN plasmid showed significantly higher levels of PTEN expression, however, the expression level of the CD47 gene has been decreased. Also, the invasion ability of tumor cells has been down-regulated. Also, we observed a negative correlation between the gene expression of the tumor suppressor gene PTEN and the CD47 and SIRPα genes. In summary, based on the anti-tumor effect of PTEN and its effect on inhibition of the bone tumor, it could be hypothesized that this phenomenon might be related to the phosphorylation of the CD47 and SIRPα gene.